1995
DOI: 10.1111/j.1365-2885.1995.tb00576.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a heavy infection with sensitive and resistant strains of Ostertagia circumcincta and with Trichostrongylus colubriformis on the pharmacokinetics of febantel in lambs

Abstract: Plasma concentrations of febantel and its major metabolites, fenbendazole, oxfendazole and fenbendazole sulphone, were determined after oral administration of 7.5 mg/kg febantel in lambs before and 28 days after infection with 100,000 L3 larvae of a benzimidazole (BZ)-sensitive or BZ-resistant strain of Ostertagia circumcincta or with 75,000 L3 larvae of a BZ-sensitive Trichostrongylus colubriformis strain. The febantel concentrations were always low, and in only a few samples were higher than the limit of det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, most pharmacokinetic studies on anthelmintics have been carried out in non-parasitized animals. The few studies performed on parasitized animals treated with oxfendazole (Hennessy et al 1993), febantel (Landuyt et al 1995) and fenbendazole (Marriner et al 1985) revealed changes in the systemic pharmacokinetics of benzimidazoles or their precursors, ending with a lower animal drug impregnation. Very few data are available on the influence of parasitism on endectocide disposition.…”
Section: Introductionmentioning
confidence: 97%
“…However, most pharmacokinetic studies on anthelmintics have been carried out in non-parasitized animals. The few studies performed on parasitized animals treated with oxfendazole (Hennessy et al 1993), febantel (Landuyt et al 1995) and fenbendazole (Marriner et al 1985) revealed changes in the systemic pharmacokinetics of benzimidazoles or their precursors, ending with a lower animal drug impregnation. Very few data are available on the influence of parasitism on endectocide disposition.…”
Section: Introductionmentioning
confidence: 97%
“…Comparable results were observed by Debackere et al (1993). Because this was published by the same research team as Landuyt et al (1995), and because the study outcomes were similar, the results of the Debackere investigation are not included in Table 2. One of the fundamental differences between the two investigations was the parasite load used to generate the artificial infections.…”
Section: Impact Of Disease As a Function Of Drug Classmentioning
confidence: 88%
“…This is an important consideration because studies of this compound involved oral drug administration and because the targeted parasites reside in the GI tract. Landuyt et al (1995) evaluated plasma concentrations of febantel, its two active metabolites and the inactive metabolite, after an oral dose of 7.5 mg/kg febantel in lambs before and 28 days after parasite infection. The pathogens were Ostertagia circumcincta [G1 = susceptible parasites (n = 5), G3 = drug resistant parasites (n = 3)] or a susceptible strain of Trichostrongulus colubriformis (G2, n = 5).…”
Section: Impact Of Disease As a Function Of Drug Classmentioning
confidence: 99%